Transcription Factor TonEBP Stimulates Hyperosmolality-Dependent Arginine Vasopressin Gene Expression in the Mouse Hypothalamus - Kim, Dong Hee; Kim, Kwang Kon; Lee, Tae Hwan; Eom, Hyejin; Kim, Jin Woo; Park, Jeong Woo; Jeong, Jin Kwon; Lee, Byung Ju (Frontiers in Endocrinology, 2021)
The hypothalamic neuroendocrine system is strongly implicated in body energy homeostasis. In particular, the degree of production and release of arginine vasopressin (AVP) in the hypothalamus is affected by plasma osmolality, and that hypothalamic AVP is responsible for thirst and osmolality-dependent water and metabolic balance. However, the osmolality-responsive intracellular mechanism within AVP cells that regulates AVP synthesis is not clearly understood. Here, we report a role for tonicity-responsive enhancer binding protein (TonEBP), a transcription factor sensitive to cellular tonicity, in regulating osmosensitive hypothalamic AVP gene transcription. Our immunohistochemical work shows that hypothalamic AVP cellular activity, as recognized by c-fos, was enhanced in parallel with an elevation in TonEBP expression within AVP cells following water deprivation. Interestingly, our in vitro investigations found a synchronized pattern of TonEBP and AVP gene expression in response to osmotic stress. Those results indicate a positive correlation between hypothalamic TonEBP and AVP production during dehydration. Promoter and chromatin immunoprecipitation assays confirmed that TonEBP can bind directly to conserved binding motifs in the 5’-flanking promoter regions of the AVP gene. This TonEBP–AVP interaction was necessary for dehydration-induced AVP transcription. Importantly, dehydration- and TonEBP-mediated hypothalamic AVP gene activation was mitigated in TonEBP haploinsufficiency mice, compared with wild TonEBP homozygote animals. Additionally, dehydration-induced reductions in body weight were rescued in TonEBP haploinsufficiency mice, independently of food intake. Altogether, our results demonstrate an intracellular machinery within hypothalamic AVP cells that is responsible for dehydration-induced AVP synthesis.